The primary health care environment and the impact on motivation and stress in nurses (Research, Society and Development, 2021)
Objective: The focus of this study was to investigate the possible occupational stress the nurses perceived that in Basic Health Units (BHUs) and assess the major factors that motivate these employees’ inside these primary healthcare centers. Methodology: Data was collected from 70 nurses working in 61 BHUs distributed in the South of Brazil. The stress was measured with the Nurses' Stress Inventory (NSI), and the determination of motivation was performed using Maslow's Hierarchy of Needs. The research has been taken up with special reference to administrative/assistance nurses. Results: The investigation showed that nurses are predominantly female (89.5%) and 80.0% work equally in assistant care and administrative functions. Moreover, the data showed that 89.4% of nurses present moderate to higher stress scores as a consequence of the intrinsic work factors. Investigating the motivation, the higher level in the Maslow hierarchy was belonging, this could be related to the fact BHUs are inserted in communities with strong social connections and relationships with the population. Conclusion: Knowing the main factors responsible for stress in nurses at the BHUs are essential for future strategies to improve working conditions.